NB-IoT Network Planning for Smart Metering Deployment in Purwokerto - Melinda Br Ginting; Noor Amelia; Solichah Larasati; Robin Sinurat (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
This study evaluates the feasibility of utilizing the 2100 MHz frequency band for the implementation of a Narrowband Internet of Things (NB-IoT) network in the Purwokerto region using two schemes, In-Band and Guard-Band. This research aims to provide recommendations for the most efficient scheme to support the implementation of Smart Metering based on Advanced Metering Infrastructure (AMI) in the area. The method used is simulation based on radio planning software, considering the number of existing sites, network capacity, and coverage. The key performance parameters analyzed include Reference Signal Received Power (RSRP), Signal to Interference plus Noise Ratio (SINR), and throughput. The simulation results show that both schemes can be used for the implementation of the NB-IoT network in Purwokerto, but the Guard-Band scheme provides better performance with RSRP of –94.39 dBm, SINR of 6.61 dB, and throughput of 14,947 bps, compared to the In-Band scheme, which results in RSRP of –99.39 dBm, SINR of 6.61 dB, and throughput of 14,623 bps. Based on these results, the Guard-Band scheme is recommended for implementation because it provides superior performance in the RSRP and throughput parameters, which are crucial for supporting the quality of Smart Metering AMI services. The contribution of this research is to provide new insights into the implementation of NB-IoT in Purwokerto and compare two frequency allocation schemes within the 2100 MHz band. Keywords: NB-IoT, Smart Metering, In-Band, Guard-Band, 2100 MHz.